As vantagens de ser invisível : uma reflexão sobre a indústria cultural e leitura literária como experiência - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The present coursework has as objective to investigate Stephen Chbosky's novel The perks of being a wallflower, as a mass cultural product and to reflect to what extent the work can promote readings as an experience, in the light of Jorge Larrosa's proposal. This is a bibliographical research in which, primarily, it was sought to characterize the cultural industry from the concepts coined by Theodor W. Adorno, Max Horkheimer and Walter Benjamin, followed by a study to relativize the emptying of meanings of the work of art in mass culture defended by the Frankfurtians. Then, it was resorted to Mikhail Bakhtin's theory on the dialogical character of language, as well as to the studies of professor Marilena Chauí about the transforming and resistance appeal implied in this type of production. The specificities of literary reading and the type of experience it promotes were discussed based on studies by Jorge Larrosa, Roland Barthes and Eliana Yunes. After including the work in the panorama of contemporary youth adult literature, it was reflected on its relationship with the Brazilian publishing market and was sought to analyze its structure, narrative procedures and themes approached. Finally, The perks of being a wallflower was analyzed in the light of the theoretical assumptions , when it was possible to observe that the work has characteristics that identify it as a mass cultural product and that it allows a significant reading experience for the teenage reader, once it introduces them to a structure that renews the tradition of the epistolary novel, while experimenting dear themes to youth, such as the experience of death, sexual initiation, drugs use and the construction of identity.
Keywords: Indústria cultural; Literatura juvenil; Leitura como experiência; As vantagens de ser invisível; Cultural industry; Young adult literature; Reading as an experience; The perks of being a wallflower; CNPQ::LINGUISTICA, LETRAS E ARTES